Low-fatigue, adjustable pressure garments at 10, 20 and 30 mm Hg reduce scar thickness and improve pliability - Danielle M. DeBruler; Molly E. Baumann; Britani N. Blackstone; Megan M. Malara; J. Kevin Bailey; Dorothy M. Supp; Heather M. Powell (PLoS ONE, 2026)
Scarring remains problematic post-burn injury even with pressure garment therapy, the current standard of care for scar suppression. Unfortunately, there is no consensus regarding the minimum pressure magnitude required for efficacy. Thus, to fill this knowledge gap, the relationship between the magnitude of applied pressure and scar outcomes was assessed using a porcine burn-excise-autograft model. Scars were treated with adjustable, low-fatigue pressure garments fit to 10, 20, or 30 mmHg; control scars were untreated (n = 16/group). Scar contraction, thickness, histological appearance, and biomechanics were assessed, and garment fatigue was measured. At all magnitudes of applied pressure, use of garments significantly reduced scar contraction and thickness, and improved scar pliability and elasticity, versus controls. Utilizing adjustable, low-fatigue garments, pressures of 10, 20, and 30 mmHg were reliably maintained throughout the study, demonstrating the efficacy of pressure garment therapy at pressures as low as 10 mmHg. While 30 mmHg pressure garments significantly reduced contraction compared to 10 or 20 mmHg, these garments required greater adjustment of the garment to reach the target pressure, which in practice could necessitate more frequent garment replacement. The results showed that although greatest improvement was observed at 30 mmHg, pressure as low as 10 mm Hg is effective at reducing post-burn scarring if that pressure is maintained throughout the garment’s use.